Towards sustainable aviation: civil aviation policies in turkey in global context - GÜRSOY HAKSEVENLER, BETÜL HANDE (My University, 2022)
IntroductionCivil aviation is defined as all aviation activities carried out for non-military purposes, such as private, sporting, or commercial. This sector has proliferated since the late 1940s globally (Addepalli et al., 2018). However, this rapid growth causes environmental degradation and brings sustainable aviation practices into the national green transition agendas ( Planès et al, 2021). This paper examines the concept of sustainability in civil aviation by (i) describing the historical background of international civil aviation (in the world and in Turkey) ii) reviewing the literature on sustainability in civil aviation (emphasis on international aviation organizations designing sustainable aviation policies, i.e. ICAO) iii) elaborating the case of Air France-KLM as a best practice example (Air France-KLM, 2022). This paper evaluates the relevant breakthroughs of the global civil aviation industry, the goals of international authorities, and Turkey\"s approach to providing suggestions for harmonizing the Turkish civil aviation industry with the globe. In the literature, it is seen that solutions to sustainability problems are mostly sought by referring to technological developments. This study states that; integrative approaches by the sectoral and policy actors need to be produced to achieve effective results in sustainable aviation. For this purpose, we made a comprehensive literature review and content analysis of the relevant documents and reports to have a snapshot of sustainable aviation practices by analyzing the related international and national policy documents for sustainable aviation such as BM ICAO CORSIA and EU Green Deal (EC, 2022). Then, Air France KLM Example is elaborated to derive the lessons learned for improving the sustainable aviation practices in Turkey. Materials and methodsWe made a comprehensive literature review and content analysis of the secondary sources of policies, regulations, and reports. The aim is to examine the application areas of the sustainable aviation concept, the targets and policies envisaged by the international civil aviation authorities through literature review and desk research on related documents.Results and discussionThe sector in Turkey is particularly successful in following the latest technologies and is enthusiastic about catching international trends. This success is mostly realized under the leadership of the private sector in order to increase their international competitiveness. The shortcomings focus on national legislation, incentives, and obligations, lack of resources, and environmental awareness. Sustainability policies in the sector are formed as a result of the effects of international obligations, competition, and related parties (stakeholders). The sector has a multi-actor structure and cooperation between actors is present and necessary. However, cooperation on sustainability issues needs to be increased.ConclusionsIt has been determined that the studies in the literature on sustainable aviation mostly progress on greenhouse gas emissions and noise pollution and offer solutions through developments such as fuel savings or new generation aircraft technology. However, these developments and suggestions cannot serve the targeted and needed sustainability purpose alone. This study draws attention to the inadequacy of reducing the approach to sustainable aviation to sectoral developments, that realistic and tangible solutions to the issue are only possible with a network chain which requires policymakers, institutions and organizations in the sector, civil actors and even non-sector actors to act together with a comprehensive and integrated approach. Acknowledgements: This study is derived from an N. Ümran Temel’s unpublished MSc. Thesis entitled \"Evaluation of Turkey\"s Civil Aviation Policy within the Scope of the Global Sustainable Aviation\" From Graduate School of Social Sciences, Marmara University/ Turkey. References: Addepalli S., Pagalday G., Salonitis K. ve Roy R. (2018), \"Socio-economic and demographic factorsthat contribute to the growth of the civil aviation industry.\" Procedia Manufacturing, 19:2-9.https://doi.org/10.1016/j.promfg.2018.01.002.Air France-KLM (2022), \"Principles\", https://www.airfranceklm.com/sites/default/files/afklm_principles_2021_en.pdfAirlines.European Commission (2021), \"Reducing emissions from aviation\", https://ec.europa.eu/clima/policies/transport/aviation_enPlanès, T. , S.Delbecq, V.Pommier-Budinger, E.Bénard ( 2021). \"Simulation and evaluation of sustainable climate trajectories for aviation\", Journal of Environmental Management, 295, 113079
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Kamu Yönetimi; Kentleşme ve Çevre Sorunları; Social Sciences and Humanities; Political Science; Public Administration; Urbanization and Environmental Problems; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; KAMU YÖNETİMİ; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; PUBLIC ADMINISTRATION; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities